Building epistemology of multicultural education to the indigenous Javanese Islam - Fauzan, Muhammad Thoriq; Rohmadi, Syamsul Huda (Linguistics and Culture Review, 2021)
This research is intended to find out the epistemological building of multicultural education in the indigenous Javanese Islam. This theme is important to be investigated because multicultural education is still considered to be lacking. This research uses qualitative research. The data used in this study were sourced from books, journals and written results related to the indigenization (pribumisasi) of Islam, Javanese culture and multicultural education. The study focused on the indigenous Javanese Islam because of the high level of multiculturalism. The results of the study were then analyzed using an interactive data analysis model. The results of the study show that multicultural education components such as integration of content with syncretic Islam, knowledge construction lead to inclusive knowledge, reduction of prejudice with Sufism, equality education with boarding school (pesantren) and culture that empowers practiced by strengthening civil society.